Re-establishing the disrupted sensorimotor loop in deafferented and deefferented people: The case of spinal cord injuries. (December 2015) - Tidoni, E.; Tieri, G.; Aglioti, S.M.
Abstract: Acting efficiently in the world depends on the activity of motor and somatosensory systems, the integration of which is necessary for the proper functioning of the sensorimotor loop (SL). Profound alterations of SL functioning follow spinal cord injury (SCI), a condition that brings about a disconnection of the body from the brain. Such disconnection creates a substantial deprivation of somatosensorial inputs and motor outputs. Consequent somatic deficits and motor paralysis affect the body below the lesion level. A complete restoration of normal functions of the SL cannot be expected until basic neuroscience has found a way to re-establish the interrupted neural connectivity. Meanwhile, studies should focus on the development of technical solutions for dealing with the disruption of the sensorimotor loop. This review discusses the structural and functional adaptive reorganization of the brain after SCI, and the maladaptive mechanisms that impact on the processing of body related information, which alter motor imagery strategies and EEG signals. Studies that show how residual functions (e.g. face tactile sensitivity) may help people to restore a normal body image are also reviewed. Finally, data on how brain and residual body signals may be used to improve brain computer interface systems is discussed in relation to the issue of how such systems may help SCI people to re-enter the world and interact with objects and other individuals. Highlights: Spinal cord injuries disrupt the normal functioning of the sensorimotor loop. Substantial deafferentation may bring about adaptive and maladaptive plasticity. The effect of brain plasticity may influence the functioning of BCI. Improvement of BCI applications should take into account brain plasticity.